2017
DOI: 10.2196/resprot.7348
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Public Health Intervention to Reduce Functional Impairment and Depressive Symptoms in Adults With Type 2 Diabetes (The SpringboarD Trial): Randomized Controlled Trial Protocol

Abstract: BackgroundDepressive symptoms are common in people with type 2 diabetes and contribute to adverse health consequences that substantially impact social and vocational function. Despite the existence of effective depression treatments, the majority of people with type 2 diabetes do not access these when needed. Web-based alternatives to more traditional psychotherapies offer a potential solution to reducing the personal and economic burdens of type 2 diabetes.ObjectiveThis paper outlines the protocol for a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This study was an adjunct to the SpringboarD Trial; a large community-based randomised controlled trial (RCT) of an online public health intervention called myCompass to increase functioning and mental health in adults with T2DM. The full trial protocol is detailed elsewhere (Proudfoot et al, 2017 participants was required to detect the medium effects observed in similar studies (Strickhouser, Zell, & Krizan, 2017). Therefore, between April and July 2018, we emailed invitations to the first 297 SpringboarD participants to complete the 12-month self-report assessment.…”
Section: Methodsmentioning
confidence: 99%
“…This study was an adjunct to the SpringboarD Trial; a large community-based randomised controlled trial (RCT) of an online public health intervention called myCompass to increase functioning and mental health in adults with T2DM. The full trial protocol is detailed elsewhere (Proudfoot et al, 2017 participants was required to detect the medium effects observed in similar studies (Strickhouser, Zell, & Krizan, 2017). Therefore, between April and July 2018, we emailed invitations to the first 297 SpringboarD participants to complete the 12-month self-report assessment.…”
Section: Methodsmentioning
confidence: 99%
“…This study is the primary outcomes evaluation of a 2-arm RCT called SpringboarD . The full protocol for the SpringboarD Trial is published elsewhere [27]. In the full SpringboarD trial, outcomes will be assessed at baseline and 3, 6, and 12 months postrandomization.…”
Section: Methodsmentioning
confidence: 99%
“…The program offers a personalized treatment plan based on an assessment of user symptoms, either at registration or at any time during program use [25,27]. The core program consists of 12 interactive CBT modules and 20 cognitive and/or behavioral variables for self-monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…Andersson and his colleagues [60] recommend to make it very clear to the client that there is a person behind the support, to present the staff behind the intervention, including names and pictures.…”
Section: Supportmentioning
confidence: 99%
“…A review on web-based treatments for depression and anxiety disorders showed positive correlation between the amount of contact spent by therapist per patient (range from none to 333 min) and the effect size (d range from 0 to 1.5) [63]. Andersson and cols [60] suggest from their experience in depression web-based interventions to spend by therapist an average of 100 min per patient for a 10-week intervention. There is still the need to study how much therapist time spend per patient is more cost-effective.…”
Section: Supportmentioning
confidence: 99%